Uji Potensi Ekstrak Kasar Teripang Laut Holothuria atra Untuk Anti Kanker Dengan Menggunakan Metode Brine Shirmp Lethality Test - Yunita Baramuli; Nickson Kawung; James JH Paulus; Inneke FM Rumengan; Billy Th Wagey; Fransin Manginsela (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The aim of this research is to test the potency of Sea cucumber crude extract Holothuria atra using the shrimp larvae Artemia salina Leach. The sample were take from waters of tateli at Minahasa District. Sample preparation and the potential test were done at biology moleculer and marien pharmacy laboratorium of Faculty of Fhiseries and Marine Science Sam Ratulangi University. The sample macerated once with ethanol for 24 hours. Extract of the sample were conentrated using rotary evaporator. Using the  Brine Shrimp Lethality Test (BSLT) method  with shrimp larvae Artemia salina, Leach. As the sample dry weight  of the sample is 420 g after macerated with ethanol then decreased to 18 g after evaporated. Probit analysis of larva mortalityt data as the indicator of anti-cancer potential shown the value LC5030.01 mg/l. Bioactive compounds of sea cucumber H. arta has potency to be develop as anti-cancer material. Keywords: Anti cancer, Sea cucumber, Holothuria atra, Artemia salina leach